Effects of furyl-dihydropyridines I on lipid peroxides of ischemic myocardium and ATPases activity of erythrocyte membranes in rats - Liu De-qiang; Pang Zhong-qing; Zhao De-hua; Sheng Bao-heng (Acta Pharmacologica Sinica, 2016)
Acute myocardial ischemia and reperfusion in rats increased glutamic oxalacetic transaminase (GOT), non-esterified fatty acid (FFA), malondialdehyde (MDA) content. Furyl-dihydropyridines I 10 mg.kg-1 decreased the release of GOT, FFA, MDA of ischemic myocardium, and prevent ischemia-reperfusion arrhythmia. Furyl-dihydropyridines I increased Na, K-ATPase activity and N-acethylneuraminic acid (NANA) content of erythrocyte membranes, inhibited Ca-ATPase activity of erythrocyte membranes in rats. The results suggested that the mechanism of protecting the ischemic-reperfused myocardium might be associated with the inhibition of cellular lipid peroxidation and Ca-ATPase activity of cell membranes.